Gestational surrogacy in Australia 2004‐2011: treatment, pregnancy and birth outcomes. (25th February 2016) - Wang, Alex Y.; Dill, Sandra K.; Bowman, Mark; Sullivan, Elizabeth A.
Abstract : Background: Information on gestational surrogacy arrangement and outcomes is limited in Australia. Aims: This national population study investigates the epidemiology of gestational surrogacy arrangement in Australia: treatment procedures, pregnancy and birth outcomes. Materials and methods: A retrospective study was conducted of 169 intended parents cycles and 388 gestational carrier cycles in Australia in 2004–2011. Demographics were compared between intended parents and gestational carrier cycles. Pregnancy and birth outcomes were compared by number of embryos transferred. Results: Over half (54%) intended parents cycles were in women aged <35 years compared to 38% of gestational carrier cycles. About 77% of intended parents cycles were of nulliparous women compared to 29% of gestational carrier cycles. Of the 360 embryo transfer cycles, 91% had cryopreserved embryos transferred and 69% were single‐embryo transfer (SET) cycles. The rates of clinical pregnancy and live delivery were 26% and 19%, respectively. There were no differences in rates of clinical pregnancy and live delivery between SET cycles (27% and 19%) and double‐embryo transfer (DET) cycles (25% and 19%). Five of 22 deliveries following DET were twin deliveries compared to none of 48 deliveries following SET. There were 73 liveborn babies following gestational surrogacy treatment, including 9 liveborn twins. Of these, 22% (16) were preterm and 14% (10) were low birthweight. Preterm birth was 13% for liveborn babies following SET, lower than the 31% or liveborn babies following DET. Conclusions: To avoid adverse outcomes for both carriers and babies, SET should be advocated in all gestational surrogacy arrangements.